Brain Metastases Mimicking Hyperostosis Frontalis Interna on 99mTc HDP Bone Scintigraphy. (October 2016) - Kang, Sae-Ryung; Kim, Jahae; Kwon, Seong Young; Min, Jung-Joon; Bom, Hee-Seung; Sohn, Myung-Hee; Song, Ho-Chun
Abstract : Abstract: Symmetric bifrontal uptake of bone-seeking agents is usually considered as the main feature of hyperostosis frontalis interna in postmenopausal elderly women. This finding is not uncommon in elderly women because of the change in their hormonal level. However, in the present case, a 66-year-old woman with intra-axial brain metastases of breast cancer showed symmetric bifrontal uptake on bone scintigraphy. Therefore, symmetric bifrontal uptake should not always be considered as a definite indicator of hyperostosis frontalis interna. Further evaluation such as SPECT/CT is needed for evaluation of brain metastases especially in cancer patients.